Formação docente: as TIC como alternativa para a experimentação no ensino de Química - Gonçalves, Luciene Pereira da Silva (2015)
The experimental activities are viewed most often as an element that arouses the curiosity of the students on the topic proposed in science classes. However, several factors prevent the experiments from happening properly, among them: the deformed views of teachers about their role in education. Based on this assumption, this study investigated the visions of future teachers on the use of experimentation in class Science / Chemistry. Participated in the research students of the Degree in Chemistry at the Federal University of Goiás, whose training needs were observed while attending the Instrumentation discipline for Teaching 1, whose focus of study: the use of experimentation in chemistry education. From problem identification, we chose to follow the methodological steps of the Participant Survey, because we deal with an educational activity of research and social action. In this regard, a training proposal is designed to be applied in Instrumentation discipline for Teaching 2, aiming to help those involved in the critical study of their problems and finding appropriate solutions to their practical classroom. As mediated action tool was used Modular Object Oriented Dynamic Learning (Moodle) which is a Virtual Learning Environments management system for the communication online. The training process took place in a virtual environment to further shape the face discipline involving discussions about the role of experimentation in teaching Sciences / Chemical and chemical concepts from video experiments, produced by the students in the discipline Instrumentation for Teaching 1. Threads of the participants were analyzed from the contributions of Derek Hodson, as a theoretical reference. Our results show that despite the subjects of this investigation being in the final stage of the course, there are still distorted views about the nature of science and the role of experiments in chemistry classes, especially with regard to the empirical-inductive and playful nature of the activity, referring to the need to insert this discussion in early course subjects. Our studies reveal that such discussions can contribute to possible changes of the visions of future teachers because of its reflective nature, argumentative and dialogical among peers, in the light of the theory. In this sense, the Moodle platform as a cultural tool is an environment conducive to promoting discussions that contribute to teacher training, promoting the exchange of experiences and critical reflection of the subjects involved in the training process.